Two NAD‐independent l‐lactate dehydrogenases drive l‐lactate utilization in Pseudomonas aeruginosa PAO1. Issue 5 (3rd September 2018) - Wang, Yujiao; Xiao, Dan; Liu, Qiuyuan; Zhang, Yipeng; Hu, Chunxia; Sun, Jinkai; Yang, Chunyu; Xu, Ping; Ma, Cuiqing; Gao, Chao
Summary: Pseudomonas aeruginosa often establishes a chronic infection in the airways of patients with cystic fibrosis (CF).l ‐Lactate is the most abundant carbon source in the CF sputum, andl ‐lactate utilization may be important for P. aeruginosa to survive in the lungs of CF patients. In this study, the key enzymes involved inl ‐lactate utilization by P. aeruginosa PAO1 were characterized using the synthetic CF sputum medium (SCFM). A highly conserved membrane‐bound NAD‐independentl ‐lactate dehydrogenase (l ‐iLDH) encoded by lldD (PA4771) and a novel flavin‐containing membrane‐boundl ‐iLDH encoded by lldA (PA2382) were both found to contribute tol ‐lactate utilization by P. aeruginosa PAO1. In addition, an lldD and lldA double mutant was incapable of growing in a medium containingl ‐lactate as the sole carbon source. This study clarifies the mechanism and importance ofl ‐lactate catabolism, and demonstrates the first Pseudomonas spp. expressing twol ‐lactate‐oxidizing enzymes.